2019
DOI: 10.1097/sla.0000000000003402
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in Older Patients Undergoing Emergency Laparotomy

Abstract: Objective: This study aimed to document the prevalence of frailty in older adults undergoing emergency laparotomy and to explore relationships between frailty and postoperative morbidity and mortality. Summary Background Data: The majority of adults undergoing emergency laparotomy are older adults (≥65 y) that carry the highest mortality. Improved understanding is urgently needed to allow development of targeted interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(107 citation statements)
references
References 28 publications
8
96
3
Order By: Relevance
“…In addition, ELF used the Clinical Frailty Score from the Canadian Study of Health and Aging, which has seven subjective categories based on a patient's functional level and degree of control over medical conditions, whereas the mFI‐5 uses five routinely available objective variables. The significant association between increasing frailty severity and increased risk of poor postoperative outcomes and loss of independence at discharge in the ELF studies is corroborated here 14,27 .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In addition, ELF used the Clinical Frailty Score from the Canadian Study of Health and Aging, which has seven subjective categories based on a patient's functional level and degree of control over medical conditions, whereas the mFI‐5 uses five routinely available objective variables. The significant association between increasing frailty severity and increased risk of poor postoperative outcomes and loss of independence at discharge in the ELF studies is corroborated here 14,27 .…”
Section: Discussionsupporting
confidence: 59%
“…Nearly one‐third of patients in this study were frail, and frailty was associated with complications, duration of hospital stay, post discharge nursing needs and readmission. The ELF (Emergency Laparotomy and Frailty) study 14 reported frailty in 20 per cent of elderly patients undergoing emergency laparotomy in the UK. The discrepancy may be due to differences in the procedures performed, as only colorectal procedures were included here 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty is a compelling indicator of mortality, LOS, and readmission within 30 days and it has been recognized as a distinct entity from increasing age alone [14][15][16]. Studies have shown that one-fifth of older adults and 16% of younger adults presented with surgical emergencies are deemed to have frailty [17][18]. It may be that a frailty assessment on admission proves more beneficial at identifying patients in need of additional care than age.…”
Section: Limitationsmentioning
confidence: 99%
“…OPSOC has a proven record of conducting high-quality research and successfully publishing results relating to outcomes for older people [29][30][31][32]. OPSOC has an international reputation, related specifically to the care of the frail older person.…”
mentioning
confidence: 99%